Dealing with insecurity - Keck, Markus; Bohle, Hans-Georg; Zingel, Wolfgang Peter (Zeitschrift für Wirtschaftsgeographie, 2012)
The article investigates underlying social mechanisms that contribute to the remarkable resilience of Dhaka’s food system with a special focus on wholesalers and their informal business networks. A relational approach to the subject matter is elaborated that understands informality as a specific governance mode of business relations that is coined by horizontal power relations, and by the implicit codification, endogenous imposition, and personalized implementation of procedural rules. Empirical evidence is presented from recent fieldwork with rice and fish wholesalers that suggests that informality, in the form of trustworthy relations and social capital, has the potential to foster the traders’ adaptive capacities and thus not only their individual business performance, but also the overall robustness of the urban food system.